2020
DOI: 10.1111/jon.12763
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of MRI Subventricular Zone Involvement and Tumor Genetics in Lower Grade Gliomas

Abstract: BACKGROUND AND PURPOSE: Glioblastomas (GBMs) that involve the subventricular zone (SVZ) have a poor prognosis, possibly due to recruitment of neural stem cells. The purpose of this study was to evaluate whether SVZ involvement by lower grade gliomas (LGG), WHO grade II and III, similarly predicts poorer outcomes. We further assessed whether tumor genetics and cellularity are associated with SVZ involvement and outcomes. METHODS: Forty-five consecutive LGG patients with preoperative imaging and next generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
(124 reference statements)
0
18
0
Order By: Relevance
“…In this study, new SVZ involvement was detected as non-enhancing hyperintensity T2-FLAIR lesions in 80.65% patients (25/31). SVZ could increase invasiveness and migratory potential because it is the source of tumor precursor stem cells [11,23]. Thus, higher incidence of SVZ involvement (83.69%) in progression group in the present study, even without post-contrast enhancement, had adverse impaction on survival outcome of LGG patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, new SVZ involvement was detected as non-enhancing hyperintensity T2-FLAIR lesions in 80.65% patients (25/31). SVZ could increase invasiveness and migratory potential because it is the source of tumor precursor stem cells [11,23]. Thus, higher incidence of SVZ involvement (83.69%) in progression group in the present study, even without post-contrast enhancement, had adverse impaction on survival outcome of LGG patients.…”
Section: Discussionmentioning
confidence: 53%
“…From the date of surgery to the date of the last follow-up or death was de ned as overall survival (OS). From the date of surgery to the date of progression or the date of the last follow-up without progression was de ned as progression free survival (PFS) [11].…”
Section: Patientsmentioning
confidence: 99%
“…Furthermore, we show that SVZ contact to the GTV is associated with a 4.3 months lower median OS in HGG patients compared to patients that do not have SVZ contact with the GTV, which is in line with findings by Berendsen et al 6 However, we are aware that this may be misleading, as the SVZ is located centrally in the brain and it is suggested that central tumor location itself is associated with worse OS. 46 We performed similar analyses for LGG patients as well, following methods of Chiang et al 8 and Liu et al 7 but we did not find a relation between SVZ contact with GTV and survival in this patient group. The outcomes may be due to our LGG patient sample size which is less than half of the sample size used in the study of Liu et al 7 Another consideration is the atypical division of WHO grades in high-and low-grade, as Chiang et al 8 included WHO III patients as LGG patients and we included WHO III patients in the HGG cohort.…”
Section: Discussionmentioning
confidence: 71%
“…46 We performed similar analyses for LGG patients as well, following methods of Chiang et al 8 and Liu et al 7 but we did not find a relation between SVZ contact with GTV and survival in this patient group. The outcomes may be due to our LGG patient sample size which is less than half of the sample size used in the study of Liu et al 7 Another consideration is the atypical division of WHO grades in high-and low-grade, as Chiang et al 8 included WHO III patients as LGG patients and we included WHO III patients in the HGG cohort.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation